Book Review of In Dialogue With Reggio Emilia: Listening, Researching, and Learning by Carlina Rinaldi - Farveh Ghafouri (Canadian Journal for New Scholars in Education, 2012)
This article comprises a book review of "In dialogue with Reggio Emilia: Listening, researching, and learning" by Carlina Rinaldi. The book is about the early childhood program of Reggio Emilia, Italy as interpreted by Carlina Rinaldi, the pedagogista and Director of the municipal schools of Reggio Emilia for 30 years. Rinaldi’s most important articles, lectures, and interviews from 1984 to 2004 are collected in the 15 chapters of this text. This book review aims to highlight for readers a unique historical and cultural experience in relation to its particular philosophical and theoretical perspectives within a wider socio-cultural and political context. Moreover, this review locates theory and practice in Reggio Emilia schools as situated within its particular context.